Successful surface water treatment. Issue 5 (September 2019) - Unknown
Abstract : Methods that remove particles using centrifugal forces do exist as an alternative to separation dependent upon the density difference, but these are limited. However, the hydrodynamic separator developed by AquaHD is free from the limitations of conventional processes.